Perceptions of Teachers about Managerial Practices of School Heads: An Exploratory Study of Sargodha Division, Pakistan - Najeeb Ullah Khan (JELM, 2023)
The public school heads have been using diverse managerial practices.Such practices are affecting teachers’ professional and psychological matters. Consequently, the public schools teachers are under stress and strain, and cannot meet the targets assigned by the school heads. The purpose of the study was to explore the school heads managerial practices in the public primary school of Sargodha division. The study was conducted using descriptive survey. Multistage sampling was used to select 806 teachers to participate in the study. Questionnaire with likerttype scale was used as research tool in collecting data from Public primary school teachers. The reliability of the questionnaire was computed after pilot testing applying Cronbach’s Alpha (.90). The analysis of the quantitative data included percentage, mean, standard deviation, independent sample t-test and ANOVA. The results for this study show that school head frequently apply autocratic managerial practices. It is recommended that the Quaid-E-Azam Academy of Educational Development (QAED) should provide training to school heads on how to build democratic behavior and relationships with teachers.